Monologue Speech in a Foreign Language Lesson - Abishova G. (Researchparks Publishing, 2022)
This article discusses the issue of monologue speech in foreign language lessons, gives characteristics to monologue speech, and provides the opinions of well-known methodologists on this topic, the purpose of teaching monologue.